2021
DOI: 10.3390/s21092966
|View full text |Cite
|
Sign up to set email alerts
|

Feedback from HTC Vive Sensors Results in Transient Performance Enhancements on a Juggling Task in Virtual Reality

Abstract: Virtual reality headsets, such as the HTC Vive, can be used to model objects, forces, and interactions between objects with high perceived realism and accuracy. Moreover, they can accurately track movements of the head and the hands. This combination makes it possible to provide subjects with precise quantitative feedback on their performance while they are learning a motor task. Juggling is a challenging motor task that requires precise coordination of both hands. Professional jugglers throw objects so that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The use of VR technology to train motor skills has been growing in popularity over the past decade. Juggling has been a prevalent motor skill that has been used to study the effects of animated VR training on real-world performance [ 52 , 53 ]. Borglund et al [ 53 ] trained two groups of participants to juggle with two balls using an animated VR simulation.…”
Section: Efficacy Of Xr Use In Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of VR technology to train motor skills has been growing in popularity over the past decade. Juggling has been a prevalent motor skill that has been used to study the effects of animated VR training on real-world performance [ 52 , 53 ]. Borglund et al [ 53 ] trained two groups of participants to juggle with two balls using an animated VR simulation.…”
Section: Efficacy Of Xr Use In Sportmentioning
confidence: 99%
“…Juggling has been a prevalent motor skill that has been used to study the effects of animated VR training on real-world performance [ 52 , 53 ]. Borglund et al [ 53 ] trained two groups of participants to juggle with two balls using an animated VR simulation. Participants in the feedback training group received timing and height performance feedback throughout the training session (200 trials and approximately 30 min in duration), whilst the control group performed the same task with no timing and height performance feedback.…”
Section: Efficacy Of Xr Use In Sportmentioning
confidence: 99%
“…HTC Vive can be used to simulate objects, forces, and interactions between objects with high realism and accuracy. Borglund et al [ 99 ] studied feedback from HTC Vive sensors and found that the use of this device resulted in transient performance enhancements in a juggling task in VR. Kayabinar et al [ 100 ] studied the effects of VAR-based, robot-assisted gait training on dual-task performance and functional measures in patients with chronic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These immersive virtual environments (iVEs) provide a strong sense of presence [31], which is defined and studied as a subjective feeling of being there in the virtual world. Once the key perceptual-cognitive components of simulation are attained, such methods are expected to evaluate and potentially promote performance in the actual real-world task [32]. The usual goal of simulations is the training-i.e., enhancement of the potential performance in the real-world tasks [30].…”
Section: Potential Of Vr Technologies For Tpementioning
confidence: 99%